Unity PF AC-DC converter in wind based turbine generator for optimal power extraction - Chua, Sock Cheng. (2011)
Due to the rapid depletion of fossil fuel resulted from the increasing demand of electrical energy, great emphasis has been placed on renewable energy sources, for instance the generation of electric energy from wind system. The wind turbine is used to capture mechanical energy from the wind and convert into electrical energy with the use of synchronous generator. The project explores the design of a Permanent Magnet Synchronous Generator (PMSG) in a variable-speed fixed-pitch Wind Turbine Generation System (WTGS). Power electronics converters, such as diode bridge rectifier and DC-DC boost converter, are employed to extract the optimal power from the wind which is subjected to fluctuation at every moment. The wind turbine is operating at the ideal condition with the help of the Maximum Power Point Tracking (MPPT) controller. In addition, maximum power from the generator can be extracted despite the fluctuation in wind speed. These control strategies are discussed in the later chapter. The Wind Turbine Generation System is modelled using Matlab-Simulink software and the simulation results are analysed together with the theoretical findings. Problems encountered as well as recommendations are discussed at the end of the report.